Retinal Microvascular Abnormalities and Cognitive Impairment: Epidemiological Findings - Zhong, MS, Wenjun (North American Journal of Medicine and Science, 2010)
Retinal microvascular abnormalities have been associated with age-related systemic processes, such as atherosclerosis, chronic inflammation, endothelial dysfunction, and other conditions. Current epidemiological studies suggested that retinal microvascular abnormalities may be associated with cognitive decline and thereby may provide a target for early detection and prevention of dementia. However, most of previous studies have been cross-sectional and provided only suggestive evidence. Future prospective studies with assessment of cognitive function on specific domains are required to further evaluate the role of retinal microvascular signs in predicting the development of aging-related cognitive decline and dementia.